Bent-core liquid crystals based on 6-substituted 3-hydroxybenzoic acid: the role of substitution and linkage group orientation on mesomorphic properties. Issue 12 (25th September 2016) - Tůma, Jiří; Kohout, Michal; Svoboda, Jiří; Novotná, Vladimíra; Pociecha, Damian
ABSTRACT: We have prepared and studied new series of bent-core liquid crystals based on laterally substituted 3-hydroxybenzoic acid. The physical properties of the materials were tuned by the type of lateral substitution in the vicinity of the carboxylic unit. Further modification was achieved by reorientation of connecting ester linkages in the elongating side arms and by changing the length of terminal alkyl chains. The physical properties of the materials were determined by differential scanning calorimetry (DSC), polarising optical microscopy and for selected compounds by x-ray diffraction analysis. The introduction of fluorine as lateral substituent leads to the appearance of a lamellar or columnar mesophase. On contrary, methyl- or chlorine-substituted compounds are mostly crystalline. We have found a strong correlation between the size of the lateral substituent and the mesogenicity of the studied materials. GRAPHICAL ABSTRACT: